Contemporary trends - The Center for Humanities (Mount Kisko, N.Y. The Center, 1986)
Deals with the development of abstract expressionism in the 1940's and describes the basics group involved: the action painters and the abstract imagists. Pop art is discussed and the future of contemporary art is examined.
VHS.
Keywords: Abstract expressionism; Painting, Modern -- 20th century; Art studies; Humanities